Poster 205: The Effect of Increased Tibial Tubercle Trochlear Groove Distance on Post-Operative Outcomes Following Anterior Cruciate Ligament Reconstruction. Issue 7 (30th July 2022) - Johnson, Emma; Hall, Anya; Clements, Ari; Bishop, Meghan; Ciccotti, Michael; Cohen, Steven; Erickson, Brandon; Paul, Ryan
Objectives: Outcomes following anterior cruciate ligament reconstruction (ACLR) are generally good/excellent. While some risk factors for poor outcomes following ACLR have been determined, there are many that remain unknown. It is unclear if an elevated tibial tubercle trochlear groove (TT-TG) distance is a risk factor for poor outcomes following ACLR. Therefore, the purpose of this study was to determine if an elevated TT-TG increases risk of failure following ACLR. The authors hypothesized that patients with an elevated TT-TG will have an increased risk of failure following ACLR. Methods: All patients who underwent primary ACLR at a single institution between July 2018-June 2019 with a minimum of 2-year follow-up were eligible for inclusion. TT-TG distance was measured on preoperative magnetic resonance imaging (MRI) scans by 2 independent investigators. Clinical outcomes, complication rates, ability to RTS, and Lysholm scores were compared between patients with a TT-TG < 12.5mm (normal) and those with a TT-TG ≥ 12.5mm (elevated). Sub-analyses comparing normal and elevated TT-TG distance were also made after isolating athletes and bone-patellar tendon-bone (BTB) graft patients. Results: Overall, 159 patients were included, 98 with normal TT-TG distance and 61 with elevated TT-TG distance. There were no differences in demographics, concomitant procedures or injury mechanism between groups. There were also no differences in rates of reinjury, post-operative complications, need for revision ACLR, or RTS rates (all p>0.05). Patients with an elevated TT-TG distance had worse post-operative Lysholm scores than patients with a normal TT-TG distance (83.0 vs. 95.0, p=0.010), and also had differing rates of subjective instability (13.1% vs. 5.1%, p=0.083) and reoperation (13.1% vs. 4.1%, p=0.060) that trended towards significant. In patients who received a bone-patellar tendon-bone (BTB) graft, an elevated TT-TG distance was associated with higher rates of subjective instability (13.0% vs. 3.0%, p=0.041), reoperation (13.0% vs. 1.5%, p=0.012), and post-operative complications (25.0% vs. 8.2%, p=0.026), as well as lower ACL psychological readiness scores (324.1 vs. 446.7, p=0.015). Conclusions: Following ACLR, patients with an elevated TT-TG distance have worse Lysholm scores with a minimum 2-year follow-up. Patients with an elevated TT-TG who underwent ACLR with BTB grafts had significantly higher rates of subjective instability, reoperation, and post-operative complications, while no differences in reinjury, complication, revision, or RTS rates were observed. Table 1. Comparison of post-operative outcomes between normal (<12.5 mm) and elevated (≥12.5 mm) tibial tubercle trochlear groove (TT-TG) distance patients. Analysis of all patients is on the left and analysis of athletes only is on the right. Table 2. Comparison of post-operative outcomes between normal (<12.5 mm) and elevated (≥12.5 mm) tibial tubercle trochlear groove (TT-TG) distance patients who received a bone-patellar tendon-bone (BTB) autograft.